Profil Klinis Tonsilitis Pada Anak di Rumah Sakit Royal Prima Tahun 2023-2025 - Praysela, Praysela; Lister, Clarissa; Lina, Juliana (Syntax Corporation, 2025)
Tonsillitis is one of the most common ENT disorders in children and may affect growth and overall quality of life. This study aimed to describe the clinical profile of pediatric tonsillitis patients at Royal Prima Hospital during 2023–2025. A retrospective descriptive observational design was used, involving 60 medical records that met the inclusion criteria. The results showed that the highest proportion of patients was aged 13–18 years (63.3%), with males being slightly more dominant (51.7%). Most patients had a normal nutritional status (70%), and the most frequent chief complaint was painful swallowing (58.3%). Physical examination revealed tonsillar enlargement predominantly at grade T3-T3 (55%). Chronic tonsillitis was more prevalent (66.7%) than acute tonsillitis (33.3%). Operative treatment was more commonly performed (55%) compared to medical therapy (45%). In conclusion, chronic tonsillitis remains a significant health issue in children, emphasizing the need for appropriate management to prevent complications and improve patient well-being.